A compensation scheme for non-ideal circuit effects in biomedical impedance sensor - Hong, Yan (2019)
The accuracy of an I/Q based biomedical impedance sensing sensor (IQBIS) suffers significantly from the PVT effects of the analog front-end, such as the amplitude errors of the stimulation signals, gain mismatches, amplitude and phase imbalances of in-phase (I) and quadrature (Q) signals, etc. These practical effects will severely impede the system performance if handled improperly. In this paper, the degradations of sensing performance by such imperfections are mathematically analyzed and quantified. Following theoretical studies, a digitally controlled correction approach is proposed to finely alleviate these impairments. The performance of the proposed scheme had been verified using Simulink and MATLAB. With the proposed error correction scheme, the accuracy is improved by at least 17 times compared to that of the typical IQBIS, for both real and imaginary values of impedance. Thus, the proposed method is very useful for IQBIS, in resisting degradation in sensing accuracies due to the process-voltage-temperature (PVT) effects.